A fail-safe magnetorheological clutch excited by permanent magnets for the disengagement of automotive auxiliaries. (November 2014) - Bucchi, F.; Forte, P.; Frendo, F.; Musolino, A.; Rizzo, R.
This work was carried out in the framework of a funded project aimed at evaluating the feasibility of an ad hoc clutch for the disengagement an auxiliary device, i.e. the vacuum pump used with the powerbrake in diesel engine vehicles, when its operation is not required. In this way it is possible to improve the overall vehicle efficiency. Strict design specifications were defined with reference to available room, torque transmission, absence of axial loads and fail-safe operation. A magnetorheological clutch with permanent magnets was conceived to fulfil the technical requirements. Different clutch geometries were compared with particular reference to the fail-safe operation and torque capabilities. After an iterative procedure, in which both mechanical design and magnetic field analyses were considered, the most promising solution was defined and a prototype was built and tested. A four-pole sliding permanent magnet was adopted to generate the magnetic field. The experimental results validated the developed models and demonstrated the feasibility developed models and demonstrate the feasibility of the proposed solution. A principle for the automatic clutch actuation is also presented.